2018
DOI: 10.1175/jas-d-17-0315.1
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Size and Intensity Changes of Hurricanes Irma and Maria (2017) from Polar-Orbiting Satellite Microwave Radiometers

Abstract: A recently refined hurricane warm-core retrieval algorithm was applied to data from multiple polar-orbiting satellites that carry the Advanced Technology Microwave Sounder (ATMS) and the Advanced Microwave Sounding Unit-A (AMSU-A) to examine the diurnal variability of the warm cores of Hurricanes Irma and Maria. These hurricanes occurred during the 2017 hyperactive Atlantic hurricane season. Compared with data gathered by dropsondes within 100–1700 km of Hurricanes Irma and Harvey, the means and standard devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…Observations by multiple polar-orbiting satellites showed that the warm core of hurricane Maria (2017) at 250 hPa was stronger at night than during the day (Tian & Zou, 2018). To determine the possible impact of the typhoon warm core in the upper troposphere on OT occurrences, we analyzed the most prominent day-night contrast of the radial distribution of the OTD for RI typhoons.…”
Section: Diurnal Variations Of Ot Occurrencesmentioning
confidence: 99%
“…Observations by multiple polar-orbiting satellites showed that the warm core of hurricane Maria (2017) at 250 hPa was stronger at night than during the day (Tian & Zou, 2018). To determine the possible impact of the typhoon warm core in the upper troposphere on OT occurrences, we analyzed the most prominent day-night contrast of the radial distribution of the OTD for RI typhoons.…”
Section: Diurnal Variations Of Ot Occurrencesmentioning
confidence: 99%
“…The results obtained in this study using COSMIC and MetOp-A/MetOp-B GPS RO-retrieved temperature and moisture to construct a climatology of the TC structures are complementary to those results obtained from other types of observations, such as polar-orbiting satellite microwave, geostationary satellite infrared, airborne radar, and aircraft dropsonde data. The TC warm-core temperature retrievals from satellite microwave temperature sounding observations are accurate in the upper troposphere but not good in the low and midtroposphere due to rain contamination in regions of heavy precipitation in TCs (Kidder et al 2000;Tian and Zou 2018).…”
Section: Discussionmentioning
confidence: 94%
“…It is suspected that the simulation may not produce enough graupel in the upper clouds, even though the WSM6 scheme included graupel. [53] used satellite microwave sounders to measure Hurricane Maria's warm core anomaly and found upper tropospheric values of 8-12 °C from 19 to 25 September 2017. Hurricane Maria's structure was analyzed by cross sections on 66.5 W at 18Z 20 September (Figure 10a,b).…”
Section: Dominica Simulation and Forecastsmentioning
confidence: 99%
“…It is suspected that the simulation may not produce enough graupel in the upper clouds, even though the WSM6 scheme included graupel. [53]…”
Section: Dominica Simulation and Forecastsmentioning
confidence: 99%